Pengaruh Edukasi Jenis Terapi Komplementer terhadap Pemilihan Jenis Terapi Komplementer - Mutmainnah Mutmainnah; St. Malka (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The neonatal period is vulnerable to various health problems, so promotive and preventive efforts are needed, one of which is through complementary therapy methods. However, maternal knowledge regarding various types of complementary therapy is still very limited, which can influence the desire to choose the appropriate therapy for the baby's needs. This study aims to disseminate the influence of education on the selection of complementary therapy types for babies. This research method uses a Quasi Experiment design with a one-group pretest and posttest design. The sample in the study amounted to 20 mothers who had babies and were selected using a purposive sampling technique. Data collection was carried out using a knowledge level questionnaire and a checklist for selecting complementary therapy types, then analyzed using the Wilcoxon test. The results of the study showed an increase in knowledge and the majority of mothers chose complementary therapy (KMC) with a value (p = 0.001). In conclusion, there is an influence of the level of knowledge on the selection of complementary therapy types for babies. Education about complementary therapy can be used as a protective strategy in maternal and child health services to increase knowledge and support maternal decision-making in choosing safe and appropriate complementary therapy for babies.